Financial Leverage And Financial Performance Before And During The Pandemic - Wisudanto Wisudanto; I Putu Gede Nuka Nandaka; Hanuf Machfirotul Rizan (Dinasti Publisher, 2025)
This study aims to examine the differences in financial performance before and during the pandemic and the effect of financial leverage on financial performance before and during the pandemic. In this study, the proxy for measuring financial performance is ROE, and the measurement of financial leverage is DAR. The sample for this study was taken using purposive sampling, and the analysis used panel data regression with EViews 9 software. The sample in this study was the manufacturing industry during the 2017–2022 period. The results of the hypothesis indicate that ROE differs before and during the pandemic using the paired Wilcoxon test. Furthermore, the results of the hypothesis of financial leverage before the pandemic using the Fixed Effect Model (FEM) test showed a positive effect on financial performance. Meanwhile, financial leverage during the pandemic using the Random Effect Model (REM) test showed a negative effect on financial performance.